PENYULUHAN PENCEGAHAN EROSI TANAH MENGGUNAKAN MEDIA BOOKLET KEPADA MASYARAKAT DI TAMAN LENTENG AGUNG PINGKAL JAKARTA SELATAN - Sucahyanto, Sucahyanto; Hijrawadi, Sony Nugratama; Prasa, Duhan Ferin; Amaliaasyifa, Dania Nur (LPPM Universitas Islam 45 Bekasi, 2024)
Taman Lenteng Agung is located in Lenteng Agung Village, Jagakarsa District, South Jakarta, DKI Jakarta. The park, which has an area of 14,000 m2, is a riparian zone. The riparian zone is a transitional space between rivers and land, which in the zone serves as a buffer from land. Several points in the Pingkal Park area are landslide-prone areas. One of the causes of intense soil movement on sloping land is a land management system that is not based on soil conservation principles. Perennials that can accommodate the soil are very limited in population on the slopes due to massive development. This community service activity aims to convey information about the function, benefits of riparian zones, erosion potential, and soil movement that can occur in Taman Pingkal. The method used in the implementation of this activity is in the form of socialization through booklet media. Participants were collected in the park and then given material through socialization by distributing booklets to activity participants. The socialization participants amounted to 15 people from the community and park managers who used the park for sports activities and recreational activities. The result obtained from this activity is that the manager and the community still do not know the functions and benefits of riparian zones, with this activity the community becomes aware of the functions and benefits of the park and has the desire to keep the park from being damaged. The use of booklet media can be an alternative for the community to obtain information about the functions and benefits of the park. Based on the results obtained from socialization activities, the dissemination of information to the community around the park needs to be expanded. The community needs to be involved in the management of the park as an open space. In addition, the attention of the local government to the sustainability and comfort of the park as an open space for the community is expected to be increased.